2017
DOI: 10.1111/1462-2920.13659
|View full text |Cite
|
Sign up to set email alerts
|

Microbial nutrient niches in the gut

Abstract: SummaryThe composition and function of the mammalian gut microbiota has been the subject of much research in recent years, but the principles underlying the assembly and structure of this complex community remain incompletely understood. Processes that shape the gut microbiota are thought to be mostly niche‐driven, with environmental factors such as the composition of available nutrients largely determining whether or not an organism can establish. The concept that the nutrient landscape dictates which organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
238
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(244 citation statements)
references
References 116 publications
(156 reference statements)
2
238
0
4
Order By: Relevance
“…Such characteristics are relevant from an ecological perspective, where theory predicts a higher diversity in dynamic systems like the gut, with nutrient availability and type fluctuating over time 56 . Using 16S amplicon sequencing, richness differences between three enterotypes were first shown in an Amish population 29 , with a cluster similar to ET B having the lowest richness, as has been recently confirmed in a large population-wide study 7 .…”
Section: Functional and Ecological Context Of Enterotypesmentioning
confidence: 99%
“…Such characteristics are relevant from an ecological perspective, where theory predicts a higher diversity in dynamic systems like the gut, with nutrient availability and type fluctuating over time 56 . Using 16S amplicon sequencing, richness differences between three enterotypes were first shown in an Amish population 29 , with a cluster similar to ET B having the lowest richness, as has been recently confirmed in a large population-wide study 7 .…”
Section: Functional and Ecological Context Of Enterotypesmentioning
confidence: 99%
“…During metamorphosis, the gastrointestinal tract experiences compartmentalization and completely divides into the stomach, duodenum, ileum, and rectum from ages 1 to 4, and each section serves a unique biological function. This compartmentalization, in addition to producing specialized microbial assemblages, may facilitate the extraction of nutrients (Pereira & Berry, ). Our study demonstrated that different microbial assemblages are present in each of these subcompartments, which appeared to agree with previous studies in other vertebrates; therefore, these subcompartments contain distinct physiochemical environments that develop diverse microbial assemblages along their total length (Keenan & Elsey, ).…”
Section: Discussionmentioning
confidence: 99%
“…). In microbial communities, genotype‐niches have also been described in function of the different availabilities of different nutrients (Pereira and Berry ) or as a function of the values of diverse functional traits (Lennon et al. ) thus describing multivariant spaces with a determined combination of nutrients availability or functional traits where a determined genotype can exist.…”
Section: Elementome and Biogeochemical Nichementioning
confidence: 99%